Pengaruh Promosi, Lokasi, dan Variasi Produk terhadap Keputusan Pembelian pada Seduhlur Coffee Kediri - Fera Zuning Ayu Ningtyas; Taufik Akbar; Zulfia Rahmawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the influence of independent variables, namely Promotion, Location, and Product Variation, on the dependent variable, Purchase Decision, at Seduhlur Coffee Kediri. The research method used is quantitative, employing multiple linear regression analysis with the assistance of SPSS version 26 software. The sampling technique applied in this study is incidental sampling, which involves selecting respondents who happen to be present and meet certain criteria at the time the research is conducted. Based on the results of data analysis, it can be concluded that the Promotion variable has a positive and significant partial effect on Purchase Decision. This indicates that the better the promotional strategies carried out, the more likely consumers are to make a purchase. Similarly, the Location variable also shows a positive and significant partial influence, suggesting that the comfort and accessibility of Seduhlur Coffee’s location play an important role in influencing consumer decisions. Product Variation is also found to have a positive and significant partial effect on Purchase Decision, meaning that a greater variety of products offered increases the likelihood of attracting consumer interest. Simultaneously, all three variables — Promotion, Location, and Product Variation — have a significant and positive influence on Purchase Decision. This research is expected to provide useful input for Seduhlur Coffee Kediri in improving its marketing strategies and service quality to encourage and increase consumer purchasing decisions.